SARS-CoV-2 Viral Load on Admission Is Associated With 30-Day Mortality. (3rd November 2020) - Bryan, Andrew; Fink, Susan L; Gattuso, Meghan A; Pepper, Gregory; Chaudhary, Anu; Wener, Mark H; Morishima, Chihiro; Jerome, Keith R; Mathias, Patrick C; Greninger, Alexander L
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral load on admission was associated with a significantly increased 30-day mortality (odds ratio [OR], 4.20; 95% CI, 1.62–10.86), and anti-SARS-CoV-2 nucleocapisid IgG seropositivity on admission trended toward a reduced 30-day mortality (OR, 0.43; 95% CI, 0.15–1.26). Reporting of quantitative SARS-CoV-2 viral load and serologic assays may offer prognostic clinical information. Abstract : A study of 181 individuals from a single community hospital found SARS-CoV-2 viral load on admission was associated with a significantly increased 30-day mortality (OR 4.20 [95% CI: 1.62-10.86]), and anti-SARS-CoV-2 IgG seropositivity on admission trended toward a reduced 30-day mortality (OR 0.43 [95% CI: 0.15-1.26]).